Neutrophils as indicators of obesity-associated inflammation: a systematic review and meta-analysis. - Gomez-Casado, Gema; Jimenez-Gonzalez, Andrés; Rodríguez-Muñoz, Alba; Tinahones-Madueño, Francisco José; González-Mesa, Ernesto Santiago; Murri, Mora (Wiley, 2024)
Introduction: The aim of this study is to evaluate and compare the suitability of rou-tine blood neutrophil values as indicators of obesity-associated inflammation.Methods: In this systematic review and meta-analysis, we assess absolute neutrophilcounts (ANCs) and neutrophil-to-lymphocyte ratio (NLR) values in subjects with andwithout obesity and analyze the weight of both parameters on the disease. Addition-ally, correlation studies between ANC and NLR with BMI, a parameter internationallyaccepted to define obesity are performed.Results: Quantitative data from 12 (ANC) and 11 (NLR) studies were included, with atotal of 4475 participants. The meta-analysis shows that while both parameters areincreased in the obesity group, ANC values present higher differences with the con-trol and less heterogeneity among studies. Additionally, unlike NLR, ANC demon-strates a positive and significant correlation with BMI.Conclusion: Overall, this meta-analysis demonstrates that ANC is a more reliable andstable parameter than NLR for the assessment of obesity-related inflammation, whichoffers clinicians a novel tool to assist in preventing complications related to obesity
Keywords: Obesidad; Neutrófilos; Inflammation; Neutrophil; Neutrophil-to-lymphocyte ratio; Obesity